Ferroptosis-Inducing Nanomedicine for Cancer Therapy - Wang, Yang; Liu, Tianfu; Li, Xiang; Sheng, Hui; Ma, Xiaowen; Hao, Liang (Frontiers in Pharmacology, 2021)
Ferroptosis, a newly iron-dependent form of regulated cell death driven by excessive lipid peroxidation, has attracted much attention in the therapy of various types of tumors. With the nanomaterials developing, emerging evidence shows the potential of ferropotosis combined with nanomaterials for cancer therapy. Recently, there has been a great deal of effort to design and develop ferroptosis-inducing nanomedicine, specially combined with the conventional or emerging therapy. Therefore, it is timely to outline the previous efforts on the ferroptosis-inducing nanomedicine and shed light on future directions for improvement and application to fight against cancer. In this review, we will elaborate on the current strategies of cancer therapy based on ferroptosis-inducing nanomedicine, summarize the design considerations of synthesis, analyze the advantages and limitations, and finally give the future perspective on the emerging field.